A JURIDICAL-NORMATIVE INQUIRY INTO THE PROCEDURAL FRAMEWORK OF LEGAL PROTECTION FOR THE POOR TO ACCESS HEALTHCARE IN INDONESIA - Kadarusman Kadarusman; Nurjannah Septyanun; Yulias Erwin (Universitas Labuhanbatu, 2026)
This article uses a juridical-normative approach to examine health access for low-income people, focusing on procedural justice as an analytical framework. It highlights the legal system's role in protecting people with low incomes regarding health access and encourages reflection on more practical applications of procedural justice principles. Legal protection in health includes preventive and repressive aspects involving the government, hospitals, and the BPJS Kesehatan. The government and hospitals are responsible for providing good health facilities and patient safety. Participants can claim compensation for negligence or errors in health services. In contrast, hospitals are liable for losses caused by the medical team. The research highlights the importance of transparency, public participation, the right to information, and equality in ensuring quality health services for participants of the BPJS Kesehatan. However, there are areas for improvement, such as limited access to information, slow settlement processes, little compensation, legal uncertainty, and protection from discrimination. To address these weaknesses, increased transparency, accessibility, and efficiency are expected. Cooperation between the government and related agencies is essential for improving the effectiveness of the legal protection system for participants.Keywords: BPJS Kesehatan; Legal Protection; Poor People, Procedural Justice